KENDALI KECEPATAN MOTOR PADA ROBOT DENGAN EMPAT RODA OMNI MENGGUNAKAN METODE PID - Aryono Priyambudi; Beny Firman; Samuel Kristiyana (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2018)
In this research has been developed a system to conrol robot which have four wheel as a base for wheeled robot contest. The type of wheel is omni-wheel, they are shapeed with same distance each other. This system comonly have no stright movement and have no consistent aim-face of the robot in open loop control. The control system in this research use PID method to control the speed of each wheel. It use to make robot can move strightly and consistent of aim-face of the robot. The test on this system show that rotation speed of each wheel are equal to set point which set to PID control. With tune the paramater of PID with manual tuning method the system get 2.81% motor speed error. And get 0.66% error of aim-face of robot from forward and backward movement.